Penetapan kadar flavonoid total ekstrak etanol 70% dan ekstrak etil asetat daun sambung nyawa (Gynura procumbens (Lour)Merr.) secara spektrofotometri UV-Vis - Rahmadani , Adevika; Ridwanto, Ridwanto; Daulay , Anny Sartika; Nasution , Haris Munandar (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Sambung nyawa leaves (Gynura procumbens L.) are a simplicia with various medicinal properties. One of the chemical compounds in sambung nyawa leaves that plays a crucial role in treatment is flavonoids. Flavonoids in sambung nyawa leaves have benefits as antihypertensive, antioxidant, antihyperglycemic, and anti-inflammatory agents. Different drying methods for simplicia affect the total flavonoid content in the extract.The stages of this research included plant material processing, the preparation of ethanol and ethyl acetate extracts, characterization tests, phytochemical screening, and the determination of total flavonoid content in the ethanol extract and ethyl acetate extract of sambung nyawa leaves using visible spectrophotometry. The extracts of sambung nyawa leaves were made using the maceration method with 70% ethanol and ethyl acetate, and the obtained extracts were concentrated using a rotary evaporator. Total flavonoid content was then determined using visible spectrophotometry. Phytochemical screening of the ethanol and ethyl acetate extracts of sambung nyawa leaves revealed the presence of chemical compounds such as alkaloids, flavonoids, saponins, tannins, and steroids/triterpenoids. The total flavonoid content in the ethanol extract was found to be 6.5149 ± 0.0314 mcg/g of sample, while the ethyl acetate extract had a total flavonoid content of 77.6695 ± 0.1199 mcg/g of sample.